SOMATIC CONSEQUENCES OF ANOREXIA NERVOSA: AN UPDATED REVIEW - Martyna Grodzińska; Piotr Sobkiewicz; Karol Poplicha; Maria Ufniarska; Aleksandra Piech; Tomasz Ufniarski; Justyna Moszkowicz; Karolina Pasierb; Patrycja Kardasz; Bartłomiej Siuzdak; Marta Jutrzenka; Patrycja Ucikalak; et al. (International Journal of Innovative Technologies in Social Science, 2025)
Anorexia nervosa is a group of symptoms based on conscious restriction of food intake. Anorexia disrupts the body's homeostasis, so that the functioning of many organs is impaired. These dysfunctions involve the neuroendocrine system, the cardiovascular system, the skeletal system, the digestive system, and the reproductive system.  Knowing the symptoms makes it possible to make an accurate diagnosis at an early stage of the disease. This is especially important given the increasing incidence and mortality rates. This article reviews the main clinical manifestations of AN. Attention is given to both pharmacotherapies and psychotherapy.The aim of the study: The purpose of this paper is to summarize the existing knowledge on mental anorexia nervosa. The article presents etiology, epidemiology, diagnosis, differentiation, clinical picture and treatment. The topic of eating disorders in pregnant women is also described.Material and method: In our article we used English databases such as PubMed and Google Scholar. We selected the articles according to key words such as eating disorders, osteoporosis, cardiomyopathy, hypoglycemia, psychotherapy, medical assessment, treatment.Conclusions: Eating disorders are a topic that unites many medical disciplines. The array of symptoms accompanying the disease clearly demonstrates the correlation of mental health with somatic health.  Negative effects affect the skeletal system, neuroendocrine system, cardiovascular system, gastrointestinal system and reproductive system. Treatment is based on the use of pharmacotherapy, mainly using SSRI group drugs, as well as psychotherapy. A particularly appreciated current, among specialists, is cognitive-behavioral therapy.